Technology Adoption under Price Undertakings - Greetje Everaert (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2003)
Economists most often analyse the effects of protectionist or antidumping policies in the context of tariffs or voluntary export restraints - the latter are very similar to quotas in fact. Antidumping policies in the European Union however make frequent use of price undertakings. Whereas the effects of tariff and quota protection on technology adoption have been demonstrated by Miyagiwa and Ohno (1995), no such analysis has been carried out for price undertakings. In contrast to previous analysis, this article shows that adoption of new technologies is always delayed under a regime of price undertakings, as compared to the case of free trade, and that this doesn't depend on whether protection is temporary or pfirmanent. Thus, our results challenge some of the conclusions of Miyagiwa and Ohno (1995) and put further doubt on the infant-industry argument for protection. We further analyse the sensitivity of the timing of technology adoption to the instrument of protection and firmulate policy recommendations on the basis of this analysis.
Keywords: F10; F13; O33; 330; Trade protection; Antidumping; Technology adoption; Price Undertaking; Protektionismus; Antidumping; Technischer Fortschritt; Unvollkommener Wettbewerb; Außenhandelspreis; Preiswettbewerb; Theorie